Comparing the Psychometric Properties of Two Physical Activity Self-Efficacy Instruments in Urban, Adolescent Girls: Validity, Measurement Invariance, and Reliability - Voskuil, Vicki R.; Pierce, Steven J.; Robbins, Lorraine B. (Frontiers in Psychology, 2017)
Aims. This study compared the psychometric properties of two self-efficacy instruments related to physical activity. Factorial validity, cross-group and longitudinal invariance, and composite reliability were examined. Methods. Secondary analysis was conducted on data from a group randomized controlled trial investigating the effect of a 17-week intervention on increasing moderate to vigorous physical activity among 5th-8th grade girls (N=1,012). Participants completed a 6-item Physical Activity Self-Efficacy scale (PASE) and a 7-item Self-Efficacy for Exercise Behaviors scale (SEEB) at baseline and post-intervention. Confirmatory factor analyses for intervention and control groups were conducted with Mplus Version 7.4 using robust weighted least squares estimation. Model fit was evaluated with the chi-square index, comparative fit index (CFI), and root mean square error of approximation (RMSEA). Composite reliability for latent factors with ordinal indicators was computed from Mplus output using SAS 9.3. Results. Mean age of the girls was 12.2 years (SD=.96). One-third of the girls were obese. Girls represented a diverse sample with over 50% indicating black race and an additional 19% identifying as mixed or other race. Both instruments demonstrated configural invariance for simultaneous analysis of cross-group and longitudinal invariance based on alternative fit indices. However, simultaneous metric invariance was not met for the PASE or the SEEB instruments. Partial metric invariance for the simultaneous analysis was achieved for the PASE with one factor loading identified as non-invariant. Partial metric invariance was not met for the SEEB. Longitudinal scalar invariance was achieved for both instruments in the control group but not the intervention group. Composite reliability for the PASE ranged from .772-.842. Reliability for the SEEB ranged from .719-.800 indicating higher reliability for the PASE. Reliability was more stable over time in the control group for both instruments. Conclusions. Results suggest that the intervention influenced how girls responded to indicator items. Neither of the instruments achieved simultaneous metric invariance making it difficult to assess mean differences in PA self-efficacy between groups. Keywords: measurement invariance, physical activity, self-efficacy, adolescents, girls